Development of an Online Learning Lesson in the Educational Technology Equipment Operation Course for Pre-Service Teachers - Nonthamand, Narin (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The objectives of this study are (1) to explore pre-service teachers’ needs in using educational technology tools for online learning, (2) to develop an online lesson about the use of educational technology tools for pre-service teachers, and (3) to compare the learning achievements before and after taking the lesson. The methodology was divided into three phases. The first phase was a needs assessment concerning the use of educational technology tools in online learning. The samples were 272 undergraduate pre-service teachers at the University of Phayao. The research instrument was a needs analysis questionnaire on the use of educational technology tools in online learning. The collected data was analyzed using Modified Priority Needs Index (PNImodified). In the second phase, an online lesson about the use of educational tools was developed. The research samples were three experts in three different fields, including instructional design, educational technology, and assessment and evaluation. The research instrument used in this phase was a suitability assessment form for the designed online lesson. Document analysis and descriptive statistics were used to analyze the data. In the third phase, the learning achievements before and after completing the lesson were compared. The samples were 112 pre-service teachers at the University of Phayao. The research instrument was a learning achievement test. The data analysis included means, standard deviations, and a t-test. The results were as follows: Regarding the needs analysis concerning the use of educational technology tools in online learning, the pre-service teachers considered that tools for completing learning tasks were the most crucial element. The data collected from open-ended questions revealed that the most critical problems experienced in online learning were learning tools and poor Internet speed. The results from the suitability test showed that the developed online lesson was overall suitable (M = 2.98, SD = .174).The pre-service teachers’ average post-test score on the achievement test on the use of educational technology tools was higher than the average pre-test score with a statistically significant difference at the .05 level.